EXPERIMENTAL STUDY ON THE EFFECT OF CHEMICAL ADMIXTURES ON THE COMPRESSIVE STRENGTH OF CONCRETE - Arif Kesuma Hardi; Sari Utama Dewi (Bulletin of Engineering Science, Technology and Industry, 2026)
Concrete is among the most often utilized building materials because to its exceptional compressive strength and longevity. Chemical additives are frequently used into concrete formulations to enhance its mechanical characteristics and building efficacy. This research empirically examined the influence of chemical additives on the compressive strength of concrete. Two concrete formulations, specifically standard concrete and concrete with chemical additives, were evaluated at curing durations of 3, 7, and 28 days following SNI 1974:2011 guidelines. The findings indicated that concrete with chemical admixtures consistently attained superior compressive strength compared to standard concrete. The mean compressive strengths of conventional concrete at 3, 7, and 28 days were 18.45 MPa, 22.30 MPa, and 29.80 MPa, respectively, whereas the corresponding values for admixture concrete were 23.90 MPa, 30.60 MPa, and 41.30 MPa. The application of chemical admixtures enhanced the compressive strength by 29.54%, 37.22%, and 38.59% during the corresponding curing durations. These results demonstrate that chemical additives significantly enhance the compressive strength of concrete and can be utilized to create high-performance concrete for structural applications.